Chapter Thematic atlas of Italian oncological research: the analysis of public IRCCS - CUCCURULLO, Corrado (Proceedings e report, 2021)
This paper has been developed in the frame of the research project "V:ALERE 2019" focused on Italian public-owned Academic Medical Centers. The main aim of the project is to provide evidence, advice, and remarks to help the agents of the public health system to address the many challenges that they face. In recent years, there is an increasing recognition of the potential value of research evidence as one of the many factors considered by policymakers and practitioners. Even more, in the case of medical science, the analysis of research and its impact is indispensable, in light of its implications for public health. The starting point for mapping a research area is to review the related scientific literature because by synthesizing past research findings, it is possible to effectively use the existing knowledge base and advance lines of future researches. In this sense, bibliometrics becomes useful, by providing a structured analysis to a large body of information, to infer trends over time, themes researched, and to show the "big picture" of extant research. In particular, in this work, we focus our attention on the scientific production of the last 20 years of the Scientific Institutes for Research, Hospitalization, and Healthcare (IRCCS "Istituto di Ricovero e Cura a Carattere Scientifico") specialized in the oncology research. IRCCS are biomedical institutions of relevant national interest that drive clinical assistance in strong relation to research activities. They are committed to being a benchmark for the whole public health system for both the quality of patient care and the innovation skills in the field of the organization. All the analyses were carried out by using the Bibliometrix, an open-source tool for quantitative research in scientometrics and bibliometrics that includes all the main bibliometric methods of analysis.